Notch signalling mediates segmentation of the Drosophila leg. - de Celis, J.F.; Tyler, D.M.; de Celis, J.; Bray, S.J. (Development, 1998)
The legs of Drosophila are divided into segments along the proximodistal axis by flexible structures called joints. The separation between segments is already visible in the imaginal disc as folds of the epithelium, and cells at segment boundaries have different morphology during pupal development. We find that Notch is locally activated in distal cells of each segment, as demonstrated by the restricted expression of the Enhancer of split mbeta gene, and is required for the formation of normal joints. The genes fringe, Delta, Serrate and Suppressor of Hairless, also participate in Notch function during leg development, and their expression is localised within the leg segments with respect to segment boundaries. The failure to form joints when Notch signalling is compromised leads to shortened legs, suggesting that the correct specification of segment boundaries is critical for normal leg growth. The requirement for Notch during leg development resembles that seen during somite formation in vertebrates and at the dorsal ventral boundary of the wing, suggesting that the creation of boundaries of gene expression through Notch activation plays a conserved role in co-ordinating growth and patterning.